Lythrum salicaria (Purple Loosestrife) Control with Herbicides: Multiyear Applications. (2nd October 2018) - Knezevic, Stevan Z.; Osipitan, O. Adewale; Oliveira, Maxwel C.; Scott, Jon E.
Abstract: This study evaluated the effectiveness of 14 herbicide treatments for purple loosestrife ( Lythrum salicaria L.) control over a period of 10 yr. The study commenced in 2000/2001 at four wetland locations in Nebraska. The evaluated herbicides included: glyphosate at 2.2 and 3.4 kg ha −1 ; 2, 4-D dimethylamine at 1.4 and 2.8 kg ae ha −1 ; triclopyr at 1.3 and 2.1 kg ae ha −1 ; imazapyr at 1.1 and 1.7 kg ae ha −1 ; metsulfuron at 0.042 and 0.084 ai kg ha −1 ; fosamine at 13.5 and 22.4 kg ai ha −1 ; triclopyr at 1.3 kg ae ha −1 plus 2, 4-D amine at 1.4 ae kg ha −1 ; and metsulfuron at 0.042 kg ai ha −1 plus 2, 4-D amine at 1.4 kg ae ha −1 . Some treatments provided excellent control (90%) that lasted only one season, while others suppressed L. salicaria growth for multiple seasons, depending on the location and the age of L. salicaria stand. Application of higher rates of glyphosate, imazapyr, and metsulfuron consistently provided excellent control (≥90%) of L. salicaria that lasted 360 d after treatment at most locations. Application of fosamine and the lower rate of 2, 4-D amine provided the least L. salicaria control at most locations. The older the L. salicaria stand, the more multiple applications of herbicides were needed to completely control L. salicaria . Generally, there were higher percentages of grasses in the 2, 4-D-, triclopyr-, and metsulfuron-treated plots compared with higher percentages of broadleaf species in the glyphosate- and imazapyr-treated plots at each location.